Animal euthanasia as a public policy to control leishmaniasis in Brazil: a critical and reflexive analysis from an anthropocentric and necropolitical perspective - Rodrigues, Larissa (2024)
The theme of this work is euthanasia in cases of animal leishmaniasis within current Brazilian public policy. The development of the relationship between human beings and other animal species in post-humanism provided new reflections on the roles of each subject in our current society. And this was reflected in the world of law, making it possible to discuss animal rights. However, even with animal protection guaranteed by the Federal Constitution, current problems still arise from obsolete thinking in social institutions. Thus, dogs enter this scenario, which are considered the main reservoirs of leishmaniasis, but are not recognized as subjects of law by the State and, therefore, suffer drastic measures with the current policy in combating this zoonosis. It is in this context, then, that this work seeks to critically analyze the legal implications of euthanasia as a public policy adopted to control leishmaniasis from both an ethical and philosophical perspective. Thus, the methodology used was an integrative literature review from a qualitative approach, as well as bibliographical and jurisprudential research on the topic. Finally, the final considerations about the research, impressions and analyzes made during the work are presented.